Practices of Professional Learning Communities - Antinluoma, Markku; Ilomäki, Liisa; Toom, Auli (Frontiers in Education, 2021)
Building professional learning communities (PLC) has become a widely recognized strategy for school development and for student achievement. Four Finnish comprehensive schools were identified as being ready to be PLCs in a previous quantitative study, and the purpose of this study was to investigate practices of PLCs in these schools. In this paper, we used data from qualitative multiple case study, which investigated practices of leadership, culture, teacher collaboration, professional learning and development. The results showed that the principals had played the main role in the progression of schools as PLCs. Principals were described as visionary leaders who had started positive progression, shared the leadership, and created commitment to common goals. The results indicated also that a change of leaders can have positive effect. Decision-making processes were participative, inclusive, democratic, and collaborative, aiming for a satisfactory level of consensus. Relationships among staff were reported as being based on mutual trust and openness, and members were encouraged to express their opinions. Common responsibility of students, peer support, encouragement and co-teaching were practiced. Co-teaching practices were identified as an effective form of collaborative work-embedded professional learning which is related to the core principles of professional learning communities. Structural conditions were reported as barriers to schools’ development as PLCs.